Atmospheric deposition of potentially toxic elements over the territory of Serbia assessed by moss biomonitoring in five-year time: 2015 vs. 2020 - Aničić Urošević Mira P.; Radnović Dragan V.; Ilić Miloš M.; Krmar Miodrag D.; Kodranov Igor D.; Relić Dubravka J.; Popović Aleksandar R. (Journal of the Serbian Chemical Society)
The presented research, performed under the framework of the ICP Vegetation program in Serbia, had a goal to provide field-based evidence of spatial patterns and temporal trends of some potentially toxic element deposition, using naturally growing moss (Hypnum cupressiforme), as a biomonitor in surveys conducted in 2015 and 2020. The results showed a decline of the element concentrations in the moss with time for Cr (42 %), Cu (39 %), Fe (22 %), Pb (10 %) and Zn (54 %), a decrease for Cd (18 %), while staying at the same level for As and V. The concentrations of examined elements in the moss samples were comparable to those found in the neighbouring countries, with the median country values often being five or more times larger than in the pollution background countries like Switzerland and Norway. Calculation of ecological implication indices generally suggested the presence of low to moderate pollution all over the study area, with severe contamination with As, Cr, Cu and Pb at some studied locations in the eastern and northern parts of the country.